Sensor-less vector control using adaptive observer scheme for controlling the performance of the induction motor / Mazhar Hussain Abbasi - Mazhar, Hussain Abbasi (2013)
Sensorless vector control technique using adaptive observer scheme is being used to control the performance of induction motor which is demonstrated by the help of matlab/simulink software; a suitable tool for vector control of AC motor. Simulation is done by using the observer which uses optimal feedback gain as an example of process from algorithm design to verification of logic. Control design scheme in vector control, accuracy of internal parameter such as resister of motor armature and inductance affects control performance. Internal parameters are used, for example, feed-forward compensator of current controller and parameters of observer model in sensor less position. The same technique also can be applied to other types of motor like PMSM. This adaptive observer is used with the field oriented control of the induction motor. It is based on using induction motor model with the estimation of the load torque besides the estimation of the stator resistance and the robustness of this adaptive observer is with respect to the variation in the resistance of stator. The performance of the suggested adaptive observer scheme is present on via numerical simulation and the obtained results from that adaptive observer show the effectiveness of suggested scheme.